{Comparison of Isoelectronic 8-HO-G and 8-NH 2 -G Derivatives in Redox Processes} - Kaloudis, Panagiotis; D'Angelantonio, Mila; Guerra, Maurizio; Spadafora, Marie; Cismaş, Crina; Gimisis, Thanasis; Mulazzani, Quinto G.; Chatgilialoglu, Chryssostomos (J. Am. Chem. Soc., 2009)
8-Oxo-7,8-dihydroguanine (8-oxo-G) is the major lesion of oxidatively generated DNA damage. Despite two decades of intense study, several fundamental properties remain to be defined. Its isoelectronic 8-aminoguanine (8-NH 2-G) has also received considerable attention from a biological point of view, although its chemistry involving redox processes remains to be discovered. We investigated the one-electron oxidation and one-electron reduction reactions of 8-oxo-G and 8-NH2-G derivatives. The reactions of hydrated electrons (eaq-) and azide radicals (N 3•) with both derivatives were studied by pulse radiolysis techniques, and the transient absorption spectra were assigned to specific tautomers computationally by means of time-dependent DFT (TD-B3LYP/6-311G**//B1B95/6-31+G**) calculations. The protonated electron adducts of 8-NH2-G and 8-oxo-G showed a substantial difference in their absorption spectra, the unpaired electron being mainly delocalized in the imidazolyl ring and in the six-membered ring, respectively. On the other hand, the deprotonated forms of one-electron oxidation of 8-NH2-G and 8-oxo-G showed quite similar spectral characteristics. In a parallel study, the one-electron reduction of 8-azidoguanine (8-N3-G) afforded the same transient of one-electron oxidation of 8-NH2-G, which represents another example of generation of one-electron oxidized guanine derivatives under reducing conditions. Moreover, the fate of transient species was investigated by radiolytic methods coupled with product studies and allowed self- and cross-termination rate constants associated with these reactions to be estimated. © 2009 American Chemical Society.